Daily changes on seasonal ecophysiological responses of the intertidal brown macroalga Lessonia spicata: Implications of climate change - Celis-Plá, Paula S. M.; Trabal, Andres; Navarrete, Camilo; Troncoso, Macarena; Moenne, Fabiola; Zúñiga, Antonio; Figueroa, Félix L.; Sáez, Claudio A. (Frontiers in Plant Science, 2022)
Global climate change is expected to have detrimental effects on coastal ecosystems, with impacts observable at the local and regional levels, depending on factors such as light, temperature, and nutrients. Shifts in dominance between primary producers that can capitalize on carbon availability for photosynthesis will have knock-on effects on marine ecosystems, affecting their ecophysiological responses and biological processes. Here, we study the ecophysiological vulnerability, photoacclimation capacity, and tolerance responses as ecophysiological responses of the intertidal kelp Lessonia spicata (Phaeophyceae, Laminariales) during a year through different seasons (autumn, winter, spring, and summer) in the Pacific Ocean (central Chile). Six different daily cycle experiments were carried out within each season. A battery of different biochemical assays associated with antioxidant responses and in-vivo chlorophyll a fluorescence parameter showed that during spring and summer, there was an increase in photosynthetic capacity in the macroalgae, although their responses varied depending on light and nutrient availability in the course of the year. Lessonia spicata showed maximal photosynthesis and a similar photoinhibition pattern in summer compared to the other seasons, and the contents of nitrate and phosphorous in seawater were less in winter. Thus, high irradiance during spring and summer displayed a higher maximal electron transport rate (ETRmax), irradiance of saturation (Ek), non-photochemical quenching (NPQmax), nitrogen and carbon contents, and photoprotector compound levels. Antioxidant activity increased also in summer, the seasonal period with the highest oxidative stress conditions, i.e., the highest level of hydrogen peroxide (H2O2). In contrast, under low irradiance, i.e., wintertime conditions, L. spicata demonstrated lower concentrations of the photosynthetic pigments such as chlorophyll a and carotenoids. Our study suggests that macroalgae that are subjected to increased irradiance and water temperature under lower nutrient availability mediated by seasonal changes (expected to worsen under climate change) respond with higher values of productivity, pigment contents, and photoprotective compounds. Thus, our findings strengthen the available evidence to predict that algae in the order Laminariales, specifically L. spicata (kelp), could better proliferate, with lower vulnerability and greater acclimation, than other marine species subject to future expected conditions associated with climate change.